Petrogenesis of Andesite in Bukitcula, Baleendah District, Southern Bandung, West Java - Asrial, Nouval Muamar; Rosana, Mega Fatimah; Fachrudin, Kurnia Arfiansyah; Nordin, Nazihah (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
Administratively, Bukitcula Lava located in the area of Baleendah, Southern Bandung, West Java . Geographically located at Longitude 107o36'00